2016
DOI: 10.1093/ehjci/jev340
|View full text |Cite
|
Sign up to set email alerts
|

Large lipid-rich coronary plaques detected by near-infrared spectroscopy at non-stented sites in the target artery identify patients likely to experience future major adverse cardiovascular events

Abstract: Detection of large LRP by NIRS at non-stented sites in a target artery was associated with an increased risk of future MACCE. These findings support ongoing prospective studies to further evaluate the ability of NIRS to identify vulnerable patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(47 citation statements)
references
References 24 publications
5
41
1
Order By: Relevance
“…The results showed that the presence of large LCP in a non-stented segment, defined by NIRS maxLCBI 4mm ≥400 at baseline, was associated with a significantly increased risk of future MACCE during follow-up (HR 10.2, 95% CI: 3.4-30.6; P < 0.001). This study, although single center, underpowered, and with limited follow-up, was consistent with the findings of ATHEROREMO-NIRS study, whereas NIRS detection of lipid burden was associated with patient-level risk of future MACCE [93].…”
Section: Assessing Plaque Vulnerability and Risk Stratificationsupporting
confidence: 86%
See 1 more Smart Citation
“…The results showed that the presence of large LCP in a non-stented segment, defined by NIRS maxLCBI 4mm ≥400 at baseline, was associated with a significantly increased risk of future MACCE during follow-up (HR 10.2, 95% CI: 3.4-30.6; P < 0.001). This study, although single center, underpowered, and with limited follow-up, was consistent with the findings of ATHEROREMO-NIRS study, whereas NIRS detection of lipid burden was associated with patient-level risk of future MACCE [93].…”
Section: Assessing Plaque Vulnerability and Risk Stratificationsupporting
confidence: 86%
“…Although these results are promising, the number of events in this trial was small, and therefore studies with larger number of events will be required for the validation of vulnerable patient detection with NIRS-IVUS imaging. A more recent NIRS-IVUS single-center registry study was conducted in 121 consecutive patients undergoing combined NIRS and IVUS imaging to evaluate the association of large lipid-rich plaques at non-stented sites in a target vessel and subsequent major adverse cardiovascular and cere-brovascular events (MACCE) [93]. The results showed that the presence of large LCP in a non-stented segment, defined by NIRS maxLCBI 4mm ≥400 at baseline, was associated with a significantly increased risk of future MACCE during follow-up (HR 10.2, 95% CI: 3.4-30.6; P < 0.001).…”
Section: Assessing Plaque Vulnerability and Risk Stratificationmentioning
confidence: 99%
“…It is also worth noting that the extended SWIR range may be considered for brain imaging based on the endogenous contrast originated from the distinctive spectral features of the tissue constituents in this region (eg, the existence of the close but not overlapping intense absorption bands of lipids at 2165 nm, proteins around 2300 nm and water near 2480 nm). In particular, taking into account a high lipid content of a brain tissue [77] and the reported use of SWIR and SWIR-II windows for IR spectroscopy to detect/localize lipids ex vivo [41][42][43] and in vivo [78][79][80][81], an approach utilizing extended SWIR region for lipid-based brain imaging can be suggested.…”
Section: Light Penetration Depthmentioning
confidence: 99%
“…Moreover, to rule out plaque rupture in survivors of SCD with non-obstructive intermediate lesion, OCT own a potential advantage over IVUS given its higher spatial resolution. Other modality such as near infrared spectroscopy could be of value in the future[7,8]. …”
Section: Discussionmentioning
confidence: 99%